Effect of heat treatment on the dimensional stability and surface properties of rubberwood - Ratnasingam, Jegatheswaran; Ioras, Florin (2010)
Heat treatment is often used to improve the dimensional stability of wood. In this study, the effects of heat treatment on the dimensional stability and surface roughness of Rubberwood (Hevea brasiliensis), subjected to heat treatment at varying temperatures and for different durations, were examined. The oven-dry density, air-dry density, and swelling properties of the heat-treated and control Rubberwood samples, were determined. A stylus method was employed to evaluate the surface smoothness of the samples. Roughness measurements, using the stylus method, were made in the direction perpendicular to the fibre. Four main roughness parameters, i.e. mean arithmetic deviation of profile (Ra), mean peak-to-valley height (Rz), root mean square roughness (Rq), and maximum roughness (Ry) obtained from the surface of wood were used to evaluate the effect of heat treatment on the surface smoothness of the specimens. Significant differences were observed (p = 0.05) for the dimensional stability and surface roughness parameters under the different heat-treatment variables used. The values of density, swelling and surface roughness decreased with increasing temperature treatment and treatment times. Therefore, heat treatment allows Rubberwood to be successfully utilized for value-added products manufacture, where dimensional stability and surface smoothness are important, such as for window frames.